Impact of metformin treatment on cobalamin status in persons with type 2 diabetes - Sundus Fituri (17945294) (2023)
Over the last decades, low vitamin B12 status has been reported in individuals with type 2 diabetes mellitus (T2DM). Metformin, the first-line therapy for lowering blood glucose, is the main driving factor behind this association. Although the relationship between vitamin B12 deficiency and metformin is well established, results of studies on the exact effect of the dose and duration of the therapy remain inconsistent. Additionally, a lack of consensus on the definition of vitamin B12 deficiency adds to the conflicting literature. The objectives of this review were to analyze and synthesize the findings on the effects of metformin dose and duration on vitamin B12 status in patients with T2DM and to outline the potential mechanisms underlying metformin’s effect on vitamin B12. Metformin therapy has adversely affected serum vitamin B12 concentrations, a marker of vitamin B12 status. The metformin usage index (a composite score of metformin dose and duration) might serve as a potential risk assessment tool for vitamin B12 screening in patients with T2DM. Considering the health implications of suboptimal vitamin B12 status, vitamin B12 concentrations should be monitored periodically in high-risk patients, such as vegans who are receiving metformin therapy for T2DM. Additionally, it is prudent to implement lifestyle strategies concurrent with metformin therapy in individuals with T2DM, promoting an overall synergistic effect on their glycemic control. Other Information Published in: Nutrition Reviews License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1093/nutrit/nuad045